Pengaruh Viral Marketing Melalui Instagram Terhadap Minat Beli Produk Camilan Khas Daerah Secara Online - Indah Handaruwati; Adhita Maharani Dewi (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2018)
This research will examine the Influence of Viral Marketing Through Instagram which consists of Messenger, Message and Environment Toward the Interest of Buy Typical Local Snack Products. The purpose of this study to describe the activities of SMEs regional snack products in promoting their products through the media instagram. Promotion through social media instagram visual displays are expected to attract interest to buy snack products. This study uses questionnaires as a research instrument to obtain data from consumers of regional snack products in Instagram. In this study the respondent's criteria is the followers active Instagram snack products typical of the region, as well as respondents must follow at least one account of regional snack products in Instagram with the number of samples planned is 200 people obtained from the spread of questionnaires online through gogle form, monkey surveys, email and directly. The results of data processing of this study show a linear simultaneous relationship between the independent variables Messenger, Message and Environment dependent variable that Interest Buy Local Products Typical Snacks. Partially any independent variables of Messenger, Message and Environment have a linear influence on variables dependent Buy Interest Typical Regional Snack Products. While the independent variables Environment has a dominant influence on variables dependent Buy Interest Snack Products Regional Typical Online compared to other independent variables. The result of multiple linear regression shows the variables of Environment influenced 51.5%, Messenger 24.1% Message 12.0% to Buy Local Area Typical Buy Interest. The results of this study are expected to contribute positively to business actors in marketing regional special snacks online, faculty in college and further research.